OPTIMALISASI PENGELOLAAN PARKIR SEKOLAH MELALUI IMPLEMENTASI APLIKASI PARKIR BERBASIS WEB: SOLUSI DIGITAL UNTUK EFISIENSI DAN TRANSPARANSI - Taufiqurrohman; Stefanus Digita Ardhiansyah; Saifuddin Salman Habibie; Gilang Alamsyah; Shabrina Nuryani Wijaya (PEMTEKDIKMAS (PENGABDIAN EKONOMI MULTIDISIPLIN TEKNOLOGI PENDIDIKAN UNTUK MASYARAKAT), 2024)
This Community Service Program (PKM) aimed to optimize parking management at TK Daaroin through the implementation of a web-based parking application that enables real-time parking space monitoring, vehicle registration, and administrative efficiency. The school faced significant challenges in manual parking management, including disorganized vehicle documentation, unclear parking space availability, and prolonged check-in/check-out processes that created congestion during peak hours. Through educational workshops and system installation, staff and parents were trained to use the digital parking application, which features user-friendly vehicle registration, QR-code verification, automated space allocation, and real-time dashboard monitoring. Post-implementation evaluation over a 4-week period demonstrated a 38% reduction in vehicle entry time, 42% improvement in parking space utilization, elimination of manual documentation errors, and high user satisfaction (89% approval rating among parents and staff). The application also generated administrative reports for analysis and future planning. This initiative represents a practical implementation of higher education’s Tri Dharma mission in supporting digital transformation of educational institutions and demonstrates that technology-based solutions, even for simple processes, can significantly enhance operational efficiency and service quality in educational settings.